Relationships between body size attitudes and body image of 4-year-old boys and girls, and attitudes of their fathers and mothers - Damiano, Stephanie R (J Eat Disord, 2015)
BACKGROUND: Body size attitudes and body image form early in life, and understanding the factors that may be related to the development of such attitudes is important to design effective body dissatisfaction and disordered eating prevention interventions. This study explored how fathers’ and mothers’ body size attitudes, body dissatisfaction, and dietary restraint are associated with the body size attitudes and body image of their 4-year-old sons and daughters. METHODS: Participants were 279 4-year-old children (46% boys) and their parents. Children were interviewed and parents completed questionnaires assessing their body size attitudes and related behaviours. RESULTS: Socially prescribed stereotypical body size attitudes were evident in 4-year-old boys and girls; however, prevalence of body dissatisfaction was low in this sample. Correlation analyses revealed that boys’ body size attitudes were associated with a number of paternal body image variables. In boys, attributing negative characteristics to larger figures and positive characteristics to thinner figures were associated with fathers having more negative attitudes towards obese persons. Attributing positive characteristics to larger figures by boys was associated with greater levels of paternal dietary restraint. In girls, attributing positive characteristics to thinner figures was only associated with greater maternal dietary restraint. CONCLUSIONS: Findings suggest the possibility that fathers’ body size attitudes may be particularly important in establishing body size attitudes in their sons. Further research is necessary to better understand the role of fathers in the development of children’s body size attitudes.